Control strategy adopted for optimization of DG parameters in the power distribution network - Nayanatara, C.; Baskaran, J. (ICCPEIC : 2017 International Conference on Computation of Power, Energy Information and Commuincation : 22-23 March 2017, 2017)
Numerous potential benefits are obtained by installing the Distributed Generation (DG) devices in the power system distributed network. The benefits seem to be exponentially increasing with proper placement of DG devices. To attain the maximum benefits it is essential to ascertain the proper location and placing of DG without which it may overshoot the base case value. Therefore the aim to optimize the size and location of DG is for proper planning and operation of DG subject to its capacity constraints. Various methods and models are recommended for the optimization problem. This paper presents an outline of the state of art problems used in analyzing the various computational techniques with the models adopted for DG devices and the mathematical function taken to achieve maximum utilization of electrical distribution network.